Tuberculosis and diabetes mellitus: sociodemographic and clinical profile in Brazilian municipalities - Aline Ale Beraldo; Rubia Laine de Paula Andrade; Érika Simone Galvão Pinto; Reinaldo Antônio da Silva-Sobrinho; Nanci Michele Saita; Aline Aparecida Monroe; Tereza Cristina Scatena Villa (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective To analyze the sociodemographic and clinical profile of tuberculosis cases with Diabetes Mellitus in Brazilian municipalities in the states of São Paulo, Paraná and Rio Grande do Norte. Method This is a cross-sectional study, whose population consisted of tuberculosis cases notified between 2010 and 2014. Data were collected from secondary sources. In the data analysis, descriptive analysis and multiple correspondence analysis techniques were used. Results The prevalence of diabetes among tuberculosis cases ranged from 4.5% to 13.4% in the municipalities. Evidence of an association was observed between tuberculosis/diabetes comorbidity and female population, age of 61 years or more, low schooling, negative HIV/AIDS, longer treatment time, self-administered treatment and cure. Conclusion The study showed a greater cure outcome in the profile of people with tuberculosis/diabetes comorbidity, even among those on a self-administered regime, which could favor the development of specific guidelines for the management of tuberculosis in these people.